Self-directed learning in an e-socioconstructivist learning environment / Foo Sze-Yeng - Foo, Sze-Yeng (2013)
Adult learners need to equip themselves with skills to stay competitive in the changing work environment of the 21st century. The teaching and learning of adult learners ought to transition from the traditional didactic school of education to embrace self-directed and social forms of learning; which are the capstones of continuous lifelong learning (Raidal & Volet, 2009) and prerequisite to successful online learning (Shapley, 2000). This study proposes a conceptual framework of a mediated activity system in developing the esocioconstructivist learning environment (eSCLE); which is a learner-centred environment incorporating the design of a physical and virtual learning space conducive for constructing knowledge and building upon existing knowledge in collaboration with others. The design of the eSCLE for self-directed learning is an attempt to promote learning that reflects the unstructured seamless nature of lifelong self-directed learning. The activity systems and the conditions that facilitate the development of self-directed learning in the context of a cohort of adult learners enrolled in an Instructional Design and Development Course is then examined. Findings from survey questionnaires, content analysis, observation and interview reveal systemic tensions faced by learners in self-directing their learning in the eSCLE. The conflicting situation must be managed with appropriate balance and discretion in order to facilitate the development of self-directed learning. Web-based technology integrated as mediating tools is able to scaffold self-directed learning in a collaborative manner; where the functional roles of both instructor and learner-determined web tools enable self-directed actions. This study provides methodological direction for the development of self-directed instructional design, providing a basis for the continuation of this line of research in future.